Commensal –decay host ecosystem with a constant replenishment to the host species - Kalyani, K (Journal of Experimental Sciences, 2012)
The present paper deals with an analytical investigation on two species commensal-host ecological model with the host has Mortality rate and is being harvested (immigrated) at a constant rate. Further, both the species are with limited resources. This model is characterized by a couple of first order non-linear ordinary differential equation. All possible, two equilibrium points are identified and a stability criterion for it is discussed. Solutions for the linearized perturbed equations are found and results are presented.